The arginine sensing and transport binding sites are distinct in the human pathogen Leishmania. - Harsh Pawar; Madhu Puri; Renana Fischer Weinberger; Rentala Madhubala; Dan Zilberstein (Public Library of Science (PLoS), 2019)
The intracellular protozoan parasite Leishmania donovani causes human visceral leishmaniasis. Intracellular L. donovani that proliferate inside macrophage phagolysosomes compete with the host for arginine, creating a situation that endangers parasite survival. Parasites have a sensor that upon arginine deficiency activates an Arginine Deprivation Response (ADR). L. donovani transport arginine via a high-affinity transporter (LdAAP3) that is rapidly up-regulated by ADR in intracellular amastigotes. To date, the sensor and its ligand have not been identified. Here, we show that the conserved amidino group at the distal cap of the arginine side chain is the ligand that activates ADR, in both promastigotes and intracellular amastigotes, and that arginine sensing and transport binding sites are distinct in L. donovani. Finally, upon addition of arginine and analogues to deprived cells, the amidino ligand activates rapid degradation of LdAAP3. This study provides the first identification of an intra-molecular ligand of a sensor that acts during infection.